THE EFFECT OF THE CHARACTER QUOTES STRATEGY ON THE STUDENTSâ€™ READING ABILITY - Evi Rosmiyati (Universitas PGRI Palembang, 2019)
The problem in this study â€œIs there any significant effect of the application of Character Quotes Strategy on the students reading ability on narrative text to the eighth grade students of PGRI junior high school of Tebedakâ€. The objective of the study was to find out whether or not there were significant effect of the application of Character Quotes Strategy on the students reading ability on narrative text to the eighth grade students of PGRI junior high school of Tebedak. The population was the eighth grade students of PGRI junior high school of Tebedak. The sample was 30 students chosen by using purposive sampling. The method used in this study was the poor experimental method. In collecting the data, the writer used written test consisted of 40 items in the form of multiple choice tests. The written test was used to collect the data and analyzed through the matched t-test. Based on the studentsâ€™ scores, it is found that it is significant effect of the application of Character Quotes Strategy on the students reading ability on narrative text to the eighth grade students of PGRI Junior High School of Tebedak. The studentsâ€™ achievement can be seen from the average of their score in pre-test it was 56.33 and the average score of post-test was 74.58. The t-obtain 14.919 exceeding 1.699 as it is critical value. In indicated that the Ho was rejected and Ha was accepted. It means that it was significant effect of the application of Character Quotes Strategy on the students reading ability on narrative text to the eighth grade students of PGRI Junior High School of Tebedak.Â Keywords: teaching reading, narrative texts, Character Quotes Strategy